5-Aminoimidazole-4-carboxamide-1-β-D-ribofuranoside-attenuates LPS/D-Gal-induced acute hepatitis in mice. Issue 7 (October 2015) - Zhou, Dan; Ai, Qing; Lin, Ling; Gong, Xianqiong; Ge, Pu; Che, Qian; Wan, Jingyuan; Wen, Aiqing; Zhang, Li
The AMP-activated protein kinase (AMPK)-mediated energy-sensing signals play important roles in reprogramming the expression of inflammatory genes. In the present study, the potential effects of the AMPK activator 5-aminoimidazole-4 - carboxamide-1-β-D -ribofuranoside (AICAR) were investigated in a mouse model with LPS/D -Gal-induced acute hepatitis. Our experimental data indicated that treatment with AICAR suppressed the elevation of plasma aminotransferases and alleviated the histopathological abnormalities in mice exposed to LPS/D -Gal. Treatment with AICAR also inhibited the LPS/D -Gal-induced up-regulation of TNF-α, NO and myeloperoxidase. In addition, the LPS/D -Gal-induced expression of pro-apoptotic factor Bax, cleavage of caspase-3, elevation of hepatic caspase-3, caspase-8, caspase-9 activities and induction of terminal deoxynucleotidyl transferase-mediated nucleotide nick-end labeling–positive cells were all suppressed by AICAR. These results suggested that the AMPK activator AICAR could attenuate LPS/D -Gal-induced acute hepatitis, which implies that AMPK might become a novel target for the treatment of inflammation-based liver disorders.